2023
DOI: 10.7554/elife.81794
|View full text |Cite
|
Sign up to set email alerts
|

Spatial frequency representation in V2 and V4 of macaque monkey

Abstract: Spatial frequency (SF) is an important attribute in the visual scene and is a defining feature of visual processing channels. However, there remain many unsolved questions about how extrastriate areas in primate visual cortex codes this fundamental information. Here, using intrinsic signal optical imaging in visual areas of V2 and V4 of macaque monkeys, we quantify the relationship between SF maps and (1) visual topography and (2) color and orientation maps. We find that in orientation regions, low to high SF … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Additionally, the highest SI belongs to the HSF-preferred profile in the early phase of the response which supports the impact of the HSF part of the input. Similar LSF-preferred responses are also reported by Chen et al (2018 ) (50ms for SC) and Zhang et al (2023 ) (3.5 - 4 secs for V2 and V4). Therefore, our results show that the LSF-preferred nature of the IT responses in terms of firing rate and recall, is not due to the weakness or lack of input source (or information) for HSF but rather to the processing nature of the SF in the IT cortex.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Additionally, the highest SI belongs to the HSF-preferred profile in the early phase of the response which supports the impact of the HSF part of the input. Similar LSF-preferred responses are also reported by Chen et al (2018 ) (50ms for SC) and Zhang et al (2023 ) (3.5 - 4 secs for V2 and V4). Therefore, our results show that the LSF-preferred nature of the IT responses in terms of firing rate and recall, is not due to the weakness or lack of input source (or information) for HSF but rather to the processing nature of the SF in the IT cortex.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings align with these observations, showing a rise in preferred SF starting at 170ms after stimulus on-set, followed by a decline at 220ms after stimulus onset. Additionally, Zhang et al (2023 ) found that LSF is the preferred band for over 40% of V4 neurons. This finding is also consistent with our observations, where approximately 40% of neurons consistently exhibited the highest firing rates in response to LSF throughout all response phases.…”
Section: Discussionmentioning
confidence: 97%
“…Many neurons are selective for both orientation and spatial frequency in primary visual cortex in macaque, yet neurons that are narrowly tuned to orientation but broadly tuned to spatial frequency, and vice versa, also may exist ( DeValois et al., 1982 ). Also, similar tuning of neurons to orientation and spatial frequency seems to be observed in V2 and V4 ( Zhang, Schriver, Hu, & Roe, 2023 ). Other models impute a circle/cylinder arrangement for orientation and spatial frequency coding in primary visual cortex ( Bressloff & Cowan, 2003 ), analogous to the doughnut/cigar pooling model, but do not fully specify the physiological underpinnings of any pooling or summation.…”
Section: Discussionsupporting
confidence: 68%
“…The foveolar core was marked by interspersed millimeter scale functional domains. Some domains preferred very high spatial frequencies (11, 15, 18 cyc/deg, higher SF not tested), higher than non-foveolar SFs mapped in primate functional imaging 38,64,65 , but consistent with high spatial frequency preferences of macaque foveolar retinal ganglion cells (15 cyc/deg 66 ; 20-40 cyc/deg 67 ). These high spatial frequency preference domains could contribute to the high acuity needs of foveolar vision 35,6870 .…”
Section: Discussionmentioning
confidence: 59%